Otoritas hadis sirah sebagai referensi yuridis-dogmatis dalam Islam - Dzikri Nirwana (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2015)
Muslims researchers make separation between legal traditions (ah}adith al-ah}kam) documented in theliterature traditions; and historical traditions (ah}ad ith al-sira) are summarized in the literature of classicalIslamic historiography. But it turns out in a number of Sirah literature, there are some traditions ofAhk} am found. In contras, in the h}adith literatures, there are also found historical tradition. From here,it can be stated that the tradition has three dimensions at once; historical dimension, categorized ashadith Sirah; juridical dimension, identified as hadith Ahk} am; and historical and juridical dimension aswell. For this latter form, the hadith can be flexible and conditional, in the sense that when it is containedin the literature historiography, categorized as h}adith Sirah, and vice versa, as contained in the Hadithliterature in the form of juridical -dogmatic,- it is categorized as a hadith al-Ah}kam. Therefore, thehadith sira patterned in two functions; justification prophetic treatise (dala’ il Nabawiyya); and juridical -dogmatic arguments (dala’il diniyyah). These two functions are the implications of the concept ofimitation of the Prophet as an integral whole, because its realization as a model of humanity , philosophicallycould not limited by space and time. Life events and behaviors Nabawiyya being operatedfrom childhood until the prophetic, always maintained from disobedience (‘ismah) , in addition to alsoendowed a number of advantages , as a sign that he is a ‘candidate’ prophets and apostles (irhas)